Cell adhesion: stochastic receptor-ligand binding under force - Bagdasar, Ovidiu (2011)
The adhesive interactions between cells and surfaces play a key role in many vital physiological processes, such as the innate immune response or wound healing, but also in targeted drug delivery and active control on the adhesion of viruses.